"Certain Uncertainty: The Role of Internal Climate Variability in Projections of Regional Climate Change and Risk Management". Issue 12 (3rd December 2020) - Deser, Clara
Abstract: Internal climate variability co‐exists with anthropogenic climate change and places limits on the accuracy of regional climate projections due to its inherent unpredictability. This "certain" uncertainty in regional projections introduced by internal variability contrasts with uncertainty resulting from structural differences amongst climate models, which is potentially reducible as climate models improve. Initial‐condition "Large Ensembles" of simulations with individual climate models provide a new perspective on the expected range of future climate change outcomes. Their value for climate risk assessment, adaptation management, and decision‐making has yet to be fully realized. Key Points: Internal climate variability introduces unavoidable uncertainty in regional climate projections due to its limited predictability Initial‐condition "Large Ensembles" conducted with global coupled climate models provide an expected range of future climate outcomes Their value for climate risk assessment, adaptation management, and decision‐making has yet to be fully realized